Intention in Using Domestic Medical Devices Based On Grounded Theory - Putra Jaya, Hamka; Soviatun, Nuria; Akhsan, Lurinjani; Heikal, Jerry (CV. Publikasi Indonesia, 2022)
The world of health cannot be separated from medical devices. This study aims to obtain an overview of interest in the use of domestic medical devices. Eleven resource persons came from users of medical devices (hospitals, health centers, dental clinics), the purchasing department of medical devices at hospitals, medical equipment technicians who repair and maintain medical devices in hospitals, domestic distributors of medical devices, and distributors of medical devices. imports were observed and interviewed in depth. This research uses grounded theory method. The study found 79 codings which were then grouped into 15 categories and grouped again into 4 themes, namely product quality, service, price, and government regulations. This study recommends the development of medical devices in terms of quality, service and price in order to compete with imported medical devices.